Comparison of sexual function between laparoscopic lateral suspension and laparoscopic sacrocervicopexy with the use of the PISQ-IR questionnaire - Malanowska-Jarema, Ewelina; Starczewski, Andrzej; Melnyk, Mariia; Fidalgo, Daniel; Oliveira, Dulce; Dubuisson, Jean (Frontiers in Medicine, 2024)
Introduction and hypothesis We aimed to analyze the quality of sexual life of patients with apical vaginal wall prolapse who had undergone laparoscopic lateral suspension (LLS) and laparoscopic sacrocolpopexy (LSC). Methods We performed a secondary analysis of sexual outcomes of a previous randomized control trial comparing LLS and LSC in 89 women with symptomatic POP stage ≥ II. We evaluated sexually active (SA) and non-sexually active women (NSA) using the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire-IUGA-Revised (PISQ-IR). Women were reviewed over a period of 1 year post-surgery. Results Analysis of the entire PISQ-IR questionnaire indicates that surgical treatment of POP resulted in an improvement of the quality of sexual life in 21 (80.76%) in the group of sexually active women after LSC and in 20 (83.33%) in the group of SA patients after LLS. In both groups of patients, dyspareunia was not observed. Conclusion In conclusion, the quality of sexual life in SA group of patients improved significantly after both surgical procedures. The quality of sexual life of surveyed women significantly improved after curing POP symptoms.